Persepsi Mahasiswa Bahasa Inggris Terhadap Microteaching Pada Mata Kuliah Magang Bagi Calon Pendidik - Deasy Yunita Siregar; Larasati Dwi Wahyuni; Tanzila Bahar; Raisa Rahmi Nst (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
This study discusses the perceptions of students in the Internship Course with a focus on the Microteaching experience in the context of English Language Education. The study aims to explore how Microteaching affects the preparation and skills of prospective English language educators, as well as its impact on students' understanding of practical theory and confidence. Through a descriptive qualitative method, data were collected from 15 English Language Education students who took the Internship Course with Microteaching activities through the use of a questionnaire. The results showed that the majority of students responded positively to the Microteaching experience, stating an increase in teaching skills (60.00%), understanding of practical theory (46.67%), and confidence (66.67%). Although some felt the need for improvement in theoretical understanding and levels of confidence, the overall results showed that Microteaching provides a clear perspective on the reality of teaching English in the field (80.00%). Thus, the Microteaching experience in the Internship Course provides a strong foundation for the development of teaching skills and understanding of practical theory, as well as increasing confidence for prospective English language educators, providing an important basis for the development of curriculum and educational programs in the future